2020
DOI: 10.1111/pcn.13162
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal dynamics of functional connectivity in first‐episode and treatment‐naive patients with obsessive–compulsive disorder

Abstract: The aim of this study was to assess the whole-brain dynamic functional connectivity of first-episode and treatment-naive patients with obsessive-compulsive disorder (OCD) and to investigate the clinical correlations of abnormal changes in dynamic functional connectivity. Methods: Twenty-nine patients in our hospital diagnosed with first-episode OCD and 29 healthy controls matched for age, sex, and education were included in our study. Resting-state functional magnetic resonance imaging scans were performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 62 publications
(159 reference statements)
2
18
1
Order By: Relevance
“…In contrast to findings in State 1, we did not find significant between‐group differences in the occurrence of States 2 and 3, or number of transitions among those states. These findings differ somewhat from findings of Liu et al (2020)), who found an altered number of transitions. The patients in their study were all first‐episode and treatment‐naive, while half of patients in our study were previously medicated.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to findings in State 1, we did not find significant between‐group differences in the occurrence of States 2 and 3, or number of transitions among those states. These findings differ somewhat from findings of Liu et al (2020)), who found an altered number of transitions. The patients in their study were all first‐episode and treatment‐naive, while half of patients in our study were previously medicated.…”
Section: Discussioncontrasting
confidence: 99%
“…This study focused on the peak FC impairment of specific networks (FPN, DMN, and SAN) rather than the whole brain, and other key indices of dFC were not obtained. Liu et al used spatial group independent component analysis (GICA) and the sliding‐window approach to assess whole‐brain dFC, and found an altered number of transitions among different dynamic states in OCD patients that correlated with obsessive–compulsive symptom severity (Liu et al, 2020). This study used a low model order GICA and did not explore alterations of dynamic topological properties.…”
Section: Introductionmentioning
confidence: 99%
“…One previous study examined temporal properties of dFNC in OCD (Liu et al, 2020 ). It is hard to directly compare the studies because the data‐driven algorithm extracted four different states in the Liu study between which the OCD group showed more frequent switching than controls, whereas our study the algorithm indicated two states with no significant difference in number of transitions.…”
Section: Discussionmentioning
confidence: 99%
“…They focused on a subset of networks (default mode network, frontoparietal network, and salience network) and did not examine whole brain connectivity patterns. Liu and colleagues examined first‐episode and treatment‐naive patients with obsessive–compulsive disorder (OCD) (Liu et al, 2020 ) and did not examine patients undergoing treatment. Neither study examined nonaffected relatives in order to examine whether dFNC patterns might serve to identify endophenotypes for OCD.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the temporal dynamic properties of functional network connectivity in the resting state have gained increased attention because a more thorough understanding of the brain's function can be obtained through its analysis (Liao et al, 2019 ). The aberrant dynamic functional network connectivity patterns emerging from this analysis have been identified as important features of many psychiatric disorders, such as schizophrenia (Wang, Zhang, Sun, Hu, & Chen, 2016 ), major depressive disorder (MDD) (Qiu et al, 2018 ) and OCD (Gürsel et al, 2020 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%